Factors Affecting the Success of Micro, Small, and Medium Enterprises (MSMEs) at Mega Park Food Courts Medan - Ahmad Fadlan; Sri Wahyuningsih; Rizky Vita Losi; Nindya Yunita; Nuri Aslami (Journal of Management and Business Innovations, 2022)
This study purposed to empirically prove that accounting information, educational background, sales turnover, business capital, the period of business, working hours, and business location partially had a significant effect on business success in MSMEs at Mega Park Food Courts Medan. This study used multiple linear regression supported by the SPSS application. The population of the study was all MSMEs at Mega Park Food Courts Medan 90 MSMEs. The sample of this study was ninety respondents as the owners of the MSMEs. This study used observation, interviews, documentation, and questionnaires to obtain the data. The study results revealed that the use of accounting information, educational background, the period of business, and working hours variables partially showed that they had a significant effect on business success for MSMEs in Mega Park Foodcourt Medan. While sales turnover, and business capital, showed that partially they had no significant effect on business success for MSMEs in Mega Park Foodcourt Medan.Keywords: Accounting information, business capital, business location, business success, educational background, period of business, sales turnover, working hours